Designing an interactive educational system - an expert based on artificial intelligence technology to develop the skills of drawing the standard scale (Journal of the College of Basic Education, 2024)
The field of teaching and learning has witnessed, in recent years, a remarkable and rapid development due to the development of technology, as modern educational software has become one of the most important and main pillars in teaching and learning development strategies, and since modern ideas and designs in learning focused on making the learner the focus of the process, so the necessity arose to review the educational content Teaching methods used and methods of evaluation in the educational process in line with modern trends to achieve reform of the educational process by taking advantage of this technological development. (Iraqi Authority for Computers and Informatics, 2015: 8(This tremendous development in information and communication technology has led to the provision of many systems, tools and means that serve the educational process and improve it in less time and with extreme accuracy, and among these systems (the expert system( It aims to provide assistance to learners by applying human knowledge and tracking data to solve educational problems that usually require human skills, and expert systems have an important and effective role not only in transferring knowledge to learners, but also in assisting teachers and policy makers in supporting and achieving educational goals, which contributes to Increasing the effectiveness of teaching and learning and improving the entire educational process )Supriyanto & Widiaty & Abdullah, 2018( In order to overcome the difficulties faced by the students of the Department of Art Education in the subject of perspective and to employ technological innovations in teaching that have the ability to reach appropriate and effective solutions through which these problems can be overcome and meet the needs and requirements of students to learn the subject, the two researchers conducted an open survey questionnaire for students who had previously studied the subject of perspective The number of them is (30) to identify the vocabulary and skillful methods that they studied and the difficulties they encountered during their study of that subject. The researchers identified the research problem in the following question: (Does the interactive educational system develop the expert designed according to artificial intelligence technology to develop the skills of drawing the standard scale(?